2006
DOI: 10.3184/030823406777980709
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Series of 2,3-Disubstituted 4H-1,4-Benzothiazines and X-ray Crystal Structure of Ethyl 7-Chloro-3-Methyl-4H-1,4-Benzothiazine-2-Carboxylate

Abstract: The reaction between 2-aminobenzenethiol and ethyl acetoacetate is studied under a variety of conditions, and a procedure for the exclusive synthesis of 1,4-benzothiazines by the neat reaction of substituted aminothiols with bketoesters and b-dicarbonyl compounds in 85-96% yield is described. With microwave heating, even when both the reactants are solid, yields are high, reaction times brief, and work-up easy. A facile reaction is also observed even in a solid-state reaction. The molecular structure of ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the present case the C@O bond length is 1.237 Å (XRD), 1.2276 (DFT). Dandia et al [63] reported this bond length as 1.343 Å and Jadeja et al [65] reported this as 1.252 Å. The …”
Section: Geometrical Parameters and First Hyperpolarizabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…In the present case the C@O bond length is 1.237 Å (XRD), 1.2276 (DFT). Dandia et al [63] reported this bond length as 1.343 Å and Jadeja et al [65] reported this as 1.252 Å. The …”
Section: Geometrical Parameters and First Hyperpolarizabilitymentioning
confidence: 94%
“…Dandia et al [63] reported corresponding bond lengths for CAN as 1.364 and 1.412 Å for similar derivative and Endredi et al [64] reported these values as 1.408 Å and 1.412 Å, and Jadeja et al [65] reported this as 1.428 Å, Tamasi et al [66] reported this as 1.378 Å, 1.377 Å and 1.397 Å. In the present case the C@O bond length is 1.237 Å (XRD), 1.2276 (DFT).…”
Section: Geometrical Parameters and First Hyperpolarizabilitymentioning
confidence: 98%